Efficacy of Vasopressin-Methylprednisolone Vs Placebo for in-Hospital Cardiac Arrest: Systematic Review - Fatimah Fatimah; Alfino Alfino; Ghina Malya Darma; Aisyah Nur Fitri (GLOBAL HEALTH SCIENCE GROUP, 2025)
Intrahospital cardiac arrest (IHCA) has a high mortality (70-90%) despite standard resuscitation. The combination of vasopressin and methylprednisolone has been proposed as an adjuvant therapy to improve Return of Spontaneous Circulation (ROSC) and patient outcomes, but evidence of its effectiveness on long-term survival remains controversial. Objective to evaluate the efficacy of vasopressin-methylprednisolone combination versus placebo in IHCA patients for ROSC, survival, and neurologic outcomes. This systematic review study used the PICO framework (Population: Cardiac Arrest In-Hospital Patients; Intervention: Vasopressin + Methylprednisolone; Comparison: Placebo; Outcome: ROSC) and Randomized Controlled Trials (RCT) study design. A search in PubMed, ScienceDirect, and Google Scholar using the keywords